Bangladesh: women and labour activism - Rahman, Shahidur (© 2008, Routledge., 2019)
This book chapter was published in the book named Women and Labor Organizing in Asia Diversity, Autonomy and Activism [© 2008, Routledge.] and the definite version is available at: https://doi.org/10.4324/9780203938225 The Article's website is at: https://www.taylorfrancis.com/books/e/9780429241390